Hydrosols of Veronica Species-Natural Source of Free Volatile Compounds with Potential Pharmacological Interest - Marija Nazlić; Karla Akrap; Dario Kremer; Valerija Dunkić (MDPI AG, 2022)
In this study, free volatile compounds (FVCs) were isolated from the water fractions (hydrosols) of 10 Croatian Veronica species obtained by hydrodistillation (HD) and microwave-assisted extraction (MAE). The use of different isolation techniques is important for the analysis of the influence of extraction conditions on the qualitative and quantitative composition of the isolated constituents. The composition of the hydrosols was analyzed using gas chromatography and mass spectrometry. The compounds β-ionone and benzene acetaldehyde were detected in all 10 Veronica hydrosols studied. E-caryophyllene was also identified in all isolates except the MAE isolate of V. arvensis L. Caryophyllene oxide was isolated in all isolates apart from the HD isolate of V. catenata Pennell. (E)-β-Damascenone is significantly present in all isolates except the MAE isolates of V. catanata and V. cymbalaria Bodard. In these two species, α-muurolol was identified in a high percentage. The same basic phytochemical constituents and compounds characteristic of a given Veronica species suggest the importance of further research. Antioxidant activity was tested for all extracts using two methods, ORAC and DPPH. Therefore, it is crucial to identify as many specialized metabolites from Veronica species as possible, especially hydrosols, which are natural products of potential pharmacological interest.